Predicting Photovoltaic Module Lifespan Based on Combined Stress Tests and Latent Heat Analysis - Woojun Nam; Jinho Choi; Gyugwang Kim; Jinhee Hyun; Hyungkeun Ahn; Neungsoo Park (Energies)
In this study, long-term reliability tests for high-power-density photovoltaic (PV) modules were introduced and analyzed in accordance with IEC 61215 and light-combined damp heat cycles, such as DIN 75220. The results indicated that post light soaking procedure, light-combined damp heat cycles caused a 3.51% power drop, while IEC standard tests (DH1000 and TC200) caused only 0.87% and 1.32% power drops, respectively. IEC 61215 failed to assess the long-term reliability of the high-power-density PV module, such as the passivated emitter rear cell. Additionally, based on the combined test, the latent heat (<semantics>Qmod</semantics>) of the module was introduced to predict its degradation rate and to fit the prediction curve of the product guaranteed by the PV module manufacturers. <semantics>Qmod</semantics> facilitates in predicting a PV module’s lifespan according to the environmental factors of the actual installation area. The <semantics>Qmod</semantics> values of the PV stations in water environments, such as floating and/or marine PVs, indicated that they would last 7.2 years more than those on a rooftop, assuming that latent heat is the only cause of deterioration. Therefore, extending module life and improving power generation efficiency by determining installation sites to minimize latent heat would be advantageous.